2014
DOI: 10.1016/j.jweia.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A study on the inclusion of forest canopy morphology data in numerical simulations for the purpose of wind resource assessment

Abstract: A series of numerical simulations of the flow over a forest stand have been conducted using two different turbulence closure models along with various levels of canopy morphology data. Simulations have been validated against Stereoscopic Particle Image Velocimetry measurements from a wind tunnel study using one hundred architectural model trees, the porosities of which have been assessed using a photographic technique.It has been found that an accurate assessment of the porosity of the canopy, and specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The LAD was used according to Shaw and Schumann [14] in combination with a mean forest height. However, the canopy morphology may also have an impact on the wind flow [39]. Unfortunately, as often this data is not available for the WindForS test site at present and, therefore, this aspect could be part of future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The LAD was used according to Shaw and Schumann [14] in combination with a mean forest height. However, the canopy morphology may also have an impact on the wind flow [39]. Unfortunately, as often this data is not available for the WindForS test site at present and, therefore, this aspect could be part of future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The source term for the dissipation, ϵ, is, fϵ=ρCdαffalse|Ufalse|ϵ[]Cϵ4βpfalse|Ufalse|2kCϵ5βd, where Cϵ4=0.9 and Cϵ5=0.9 are model constants. Desmond et al and some others have used this model and it has been verified as an accurate assessment of the porosity of the forest canopy . The choice of values of the coefficients in the source terms equations are adopted from references …”
Section: Modelling Approachesmentioning
confidence: 99%
“…Series of numerical studies have been carried out on the simulations of wind flow over forest . In most of these studies, the forest canopy features have been explicitly represented in the simulation domain using the leaf area density (LAD).…”
Section: Introductionmentioning
confidence: 99%
“…Meroney (1970) used architectural plastic model trees, Brunet et al (1994) used flexible nylon wire, Sanz Rodrigo et al (2007) blocks of rubber foam, Lee and Lee (2012) used real miniature fir trees, and Desmond et al (2014) used rigid architectural model trees.…”
Section: Forest Modellingmentioning
confidence: 99%
“…To mimic the higher leaf density in the tree crown of a real forest, the upper part of each ring was rolled-up to increase the solidity. The Leaf Area Density (LAD) profile obtained (see Desmond et al (2014)) is shown in Fig. 4 (b).…”
Section: Forest Modellingmentioning
confidence: 99%